Social aspects of a user-friendly digital library a study on eLibrary Manila - Abejuela, Aileen P. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Research and study on digital libraries are not restricted to those who are engaged in the technical aspects and system components but it involves social aspects as well. With these technical and social aspects, guidelines were formulated for some digital libraries abroad. These guidelines are meant to serve as reference in the development of digital libraries. Focusing on the social aspects of a user-friendly digital library (since there are fewer studies on this than on the technical aspects), this study developed evaluation parameters for a user-friendly digital library in the Philippines. The evaluation parameters (which served as guidelines) were applied to eLibrary Manila (ELM), the self-proclaimed digital library managed by the researcher. The guideline were based on the Digital Library Reference Model (DLRM) Conformance Checklist and the Evaluation of Digital Libraries : a User-Friendly Guide by Reeves Thomas (2005). Prior to these, a user survey was conducted through an online questionnaire to 100 ELM members to which 28 had responded. The study proceeded as it exceeded the required 25% sample size of the population. The survey included an analysis on the digital library's contents, users, functions, policies, and its service and usability.